In Vitro Antibacterial Study of Boerhavia Diffusa L. Root Extract on Slaughterhouse Isolate Bacillus Cereus Gd55 - E, Venkatanagaraju; G, Divakar (The International Journal of Biotechnology, 2015)
The predominance of drug-resistant pathogens have extended the devotion of pharmaceutical and scientific communities towards potential antimicrobial agents from plant derived sources. The present research work has commenced to study the antimicrobial activity of the methanolic extract of Boerhavia diffusa L. roots against slaughterhouse isolate Bacillus cereus GD55, by using the agar well diffusion method. Inhibition zones ranged between 17.68 ± 0.22 mm. The root extract inhibited the growth of Bacillus cereus GD55. The standard antibiotic chloramphenicol found to have a zone of inhibition 20.72 ± 0.26 mm at the concentration of 30 µg/ml. In divergence, the inhibition zone of methanol (negative control) was almost zero for testing microorganism. The spectrum activity of methanolic extract of this plant could be a possible source to obtain new and effective herbal medicines to treat various bacterial diseases.